2011
DOI: 10.1038/ejcn.2010.282
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in maternal total cholesterol and triglyceride levels during pregnancy: the contribution of demographics, behavioural factors and clinical characteristics

Abstract: Background/Objectives: Lipid disturbances during pregnancy may lead to early onset of metabolic diseases in the offspring. However, there is little knowledge on ethnic differences in lipid levels during pregnancy. We evaluated ethnic differences in non-fasting total cholesterol (TC) and triglyceride (TG) levels during early gestation and the role of demographics, behavioural factors and clinical characteristics. Subjects/Methods: Non-diabetic pregnant women (N ¼ 3025) from the Amsterdam Born Children and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 44 publications
6
32
3
1
Order By: Relevance
“…Ethnic differences in lipids have been described both in the nonpregnant (31) and the pregnant state (32), and the relationship between maternal lipids and pregnancy outcomes has been shown to vary between ethnicities (33). It is therefore difficult to compare directly between studies, even in women with the same underlying medical condition, and a more reliable comparison can only be made between groups within the same study under similar sampling conditions (Supplementary Table 1).…”
Section: Maternal Obesitymentioning
confidence: 99%
“…Ethnic differences in lipids have been described both in the nonpregnant (31) and the pregnant state (32), and the relationship between maternal lipids and pregnancy outcomes has been shown to vary between ethnicities (33). It is therefore difficult to compare directly between studies, even in women with the same underlying medical condition, and a more reliable comparison can only be made between groups within the same study under similar sampling conditions (Supplementary Table 1).…”
Section: Maternal Obesitymentioning
confidence: 99%
“…In this regard, other potential targets such as lifestyle behaviors [sedentary time (ST) and physical activity (PA)] might help pregnant women to control and regulate immunometabolic responses during early pregnancy. 4,[11][12][13][14] To date, two studies 12,15 have suggested that ST is not associated with any immunometabolic marker during early pregnancy. Furthermore, maintaining appropriate PA levels during early pregnancy seems to be associated with lower risk of developing gestational diabetes mellitus (GDM), better insulin sensitivity, and lower plasma triglycerides and total cholesterol concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, maintaining appropriate PA levels during early pregnancy seems to be associated with lower risk of developing gestational diabetes mellitus (GDM), better insulin sensitivity, and lower plasma triglycerides and total cholesterol concentrations. 4,13,14 However, the role of PA on inflammatory cytokines during early pregnancy is not clear. 12 Thereby, previous literature 4,16 has highlighted that more evidence is imperative regarding the impact of ST and PA (intensity, frequency, and duration) on immunometabolic health.…”
Section: Introductionmentioning
confidence: 99%
“…The examination of ethnicity in the current analyses is a post hoc subgroup analysis and thus needs to be treated with caution. However, ethnic differences in the relationship between insulin resistance, body adipose stores (26), lipids (27,28), and adipokines (29,30) have been reported before, and ethnic differences in lipid and lipoprotein metabolism have also been described in pregnancy (31,32). It is also possible that there are ethnic variations in the metabolism of or pharmacological response to metformin (3335).…”
Section: Discussionmentioning
confidence: 98%